(untitled) (Boletin Médico de Postgrado, 2020)
A retrospective descriptive study was performed in order to search for epidemiological data of respiratory infections by Pseudomonas aeruginosa in pediatric patients that were attended at the Unidad Funcional of Fibrosis Quística and Pediatric Service of Hospital Dr. Luis Gómez López in Barquisimeto, Lara state during the 2010-2015 period. Eighty-three medical chart records of patients met the inclusion and exclusion criteria. The majority of patients attended during 2010-2011 were between 12 and 17 years old; after 2014, most patients were under 5 years. Male sex was predominant in 2010 and 2011; in the year 2012, female patients were predominant. The highest percentage of patients came from Lara state. Sputum sample culture was the most used test to diagnose Pseudomonas infection in patients in the first four years of life. From 2010 to 2012, 100% of the patients were hospitalized. The goal of this study was to provide epidemiological data of respiratory infections by Pseudomonas aeruginosa in pediatric patients in order to design treatment strategies to improve the quality of life and longevity of these patients.